Quadruples of orthoprojectors connected by a linear relationship - Yusenko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
In the explicit form, we deduce formulas for all quadruples of orthoprojectors P_1, P_2, P_3, and P_4 irreducible to within unitary equivalence and connected by the linear relationship α_1 P_1 + α_2 P_2 + α_3 P_3 + α_4 P_4 = λ I, where (α_1, α_2, α_3, α_4) ∈ ℝ^+.